Structure of ground-dwelling arthropod assemblages in vegetation units of Área Natural Protegida Península Valdés, Patagonia, Argentina - Martínez, Fernando Joaquín (2018)
Knowing the spatial variation of insect and arachnid assemblages and their relationship with habitat variables is critical to understand the structure and dynamics of these communities in arid environments. The aim of this paper was to analyze the variation in ground-dwelling arthropod assemblages across three representative vegetation units of the Área Natural Protegida Península Valdés (Patagonia, Argentina). We asked whether environmental differences among representative vegetation units were associated to distinct arthropod assemblages. We selected three plant communities: grass, dwarf-shrub, and shrub steppes, and established three sampling sites within each of them. We measured variables of vegetation structure and soil characteristics and collected the arthropods using 10 pitfall traps per site. We analyzed the structure of arthropod assemblages at both family and ant species taxonomic levels. Each plant community displayed a distinctive assemblage, with differences in diversity, taxa abundance, trophic structure and functional groups of ants. Vegetation variables explained a higher proportion of the variation in the structure of the ground-dwelling arthropod assemblages than the soil variables. This work highlights the importance of the different vegetation units for the conservation of ground-dwelling arthropod biodiversity in Península Valdés.